Exploring integration issues in A blended Mobile Learning model context oriented applied to an information systems course curriculum: mobility, context and cloud - Moreira, Fernando (2018)
The increasing number of mobile devices in day-to-day of general population and particularly among younger people, leads to emergence of new paradigms in several areas of activity, particularly in education. As an example of a new paradigm in the teaching-learning can be invoked that mobile learning, such as technologies did not stop and progressed to become part of the Blended Learning Mobile model. In this paper and in the context of three-year courses Bologna Process European Degree structure at school, in Portugal, following the Curriculum Guidelines for Undergraduate Degree in Information Systems for ACM/AIS, we intend to extend our BML Context Oriented Model to Information System course, i. e. cover different areas of expertise of these courses, including Requirements Engineering.